2023
DOI: 10.1038/s41598-023-35858-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lifestyle factors with the outcome of menstrual disorders among adolescents and young women in West Bengal, India

Abstract: Menstruation is a natural phenomenon for every female, starting from adolescents to menopausal age. Any disturbances in menstrual patterns can eventually affect one’s physical as well as psychological health which in turn hamper the quality of life of women. Several factors including genetic predisposition as well as lifestyle modifications adversely affect normal menstrual patterns. Hence, this study aims to evaluate the prevalence of menstrual disorders among adolescents and young women as well as the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Over the last 2 decades, the global burden of PCOS-related infertility has grown dramatically [18]. A study showed the same observation as that of Dhar et al [14], at 30 years of age and those with a prior diagnosis of PCOS were 4 times more likely to have reported difficulties becoming pregnant than those undiagnosed and regularly sought medical treatment [19].…”
Section: P a G E |mentioning
confidence: 79%
See 1 more Smart Citation
“…Over the last 2 decades, the global burden of PCOS-related infertility has grown dramatically [18]. A study showed the same observation as that of Dhar et al [14], at 30 years of age and those with a prior diagnosis of PCOS were 4 times more likely to have reported difficulties becoming pregnant than those undiagnosed and regularly sought medical treatment [19].…”
Section: P a G E |mentioning
confidence: 79%
“…It is terrible that women are still not completely aware of their reproductive health. In our previous survey, we discovered that the majority of the population is unaware of their menstrual health while experiencing a few symptoms such as irregular menstruation, dysmenorrhea, and so on [14]. The condition stays the same in both developing and developed nations, and this could be related to traditional and cultural views [15][16][17].…”
Section: P a G E |mentioning
confidence: 99%
“…It is also known that exercise and regular aerobic physical activity are associated with better regulation of insulin in women, whose receptors are expressed in the ovary and, therefore, can influence the menstrual cycle 27 ; therefore, it could be beneficial in the prevention and control of AUB. 28 However, excessive physical activity is among the risk factors for AUB. 23 In women who practice resistance and anaerobic sports, we found Open access the highest frequencies of AUB, with 71.0% and 76.5%, respectively in each group.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, there is a considerable connection between dietary choices and PCOS. Unhealthy eating habits have been identified by Dhar et al [40] as a substantial risk factor for menstrual disorders. The likelihood of menstrual irregularities in PCOS patients can be considerably reduced by adopting healthy eating, sleeping, and exercise routines, among other lifestyle adjustments.…”
Section: Menstrual Dysfunctionmentioning
confidence: 99%